2014
DOI: 10.3389/fpsyg.2014.01041
|View full text |Cite
|
Sign up to set email alerts
|

Examining cultural drifts in artworks through history and development: cultural comparisons between Japanese and western landscape paintings and drawings

Abstract: Research on cultural products suggest that there are substantial cultural variations between East Asian and European landscape masterpieces and contemporary members' landscape artwork (Masuda et al., 2008c), and that these cultural differences in drawing styles emerge around the age of 8 (Senzaki et al., 2014b). However, culture is not static. To explore the dynamics of historical and ontogenetic influence on artistic expressions, we examined (1) 17–20th century Japanese and Western landscape masterpieces, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…A broad developmental study is critical both for answering the questions raised above and for understanding the developmental course of the cross-cultural differences observed in adults. Cultural differences could be exaggerated at early stages of development and decrease with age (see Nand, Masuda, Senzaki & Ishii, 2014) or they could be the early beginnings of what will become stable larger differences. What the present results tell are three-fold: Cultural differences in visual processing are evident by 3 years of age; the differences are evident in object recognition not just scene processing; and these differences are evident in a suite of tasks that contrasted object recognition via piecemeal features versus configural processing.…”
Section: Resultsmentioning
confidence: 99%
“…A broad developmental study is critical both for answering the questions raised above and for understanding the developmental course of the cross-cultural differences observed in adults. Cultural differences could be exaggerated at early stages of development and decrease with age (see Nand, Masuda, Senzaki & Ishii, 2014) or they could be the early beginnings of what will become stable larger differences. What the present results tell are three-fold: Cultural differences in visual processing are evident by 3 years of age; the differences are evident in object recognition not just scene processing; and these differences are evident in a suite of tasks that contrasted object recognition via piecemeal features versus configural processing.…”
Section: Resultsmentioning
confidence: 99%
“…Under the rubric of "cultural products" (Morling & Lamoureaux, 2008), researchers have begun to investigate cultural variations in human-made cultural resources that convey dominant cultural messages. Such resources include media reports, social networking sites, newspaper articles, children's stories, magazine advertisements, picture books, textbooks, and music lyrics (e.g., Huang & Park, 2013;Imada, 2012;Imada & Yussen, 2012;Kim & Markus, 1999;Markus, Uchida, Omoregie, Townsend, & Kitayama, 2006;Masuda, Gonzalez, et al, 2008;Masuda, Wang, Ito, & Senzaki, 2012;Nand et al, 2014;Snibbe & Markus, 2005;Tsai, Louie, Chen, & Uchida, 2007;Wang et al, 2012). So far, research on cultural products has focused on archival data, and researchers have analyzed these data qualitatively and quantitatively using coding schemes and investigated the association between cultural products and cultural messages.…”
Section: Future Research Is Needed To Further Scrutinize (1) Which Mementioning
confidence: 99%
“…Nand and colleagues (2014) speculate that young children may seek to internalize dominant cultural norms but become prone to seek alternative values as they enter adolescence, and adults may resume the culturally normative behavioral patterns. In line with this idea, it is possible that Chinese (vs. American) adolescents in the current study scored higher on central features because the effect of cultural socialization of sensitivity to context may not be as salient during this stage of development, thereby minimizing variations among adolescents' expression across cultures (Kuwabara & Smith, 2016;Nand et al, 2014).…”
Section: Contextual Featuresmentioning
confidence: 61%
“…The discrepancy between the current and prior findings may be attributed to participants' age and their varying degree of internalization of cultural socialization. Extending the work of Senzaki and colleagues (2014), Nand, Masuda, Senzaki, and Ishii (2014) demonstrated that cultural variability in the drawing features between Japanese and Canadian may vary across the developmental stage, such that cultural differences in aspects of drawing were found in elementary school children and young adults, while cultural similarities were evident in adolescents. Nand and colleagues (2014) speculate that young children may seek to internalize dominant cultural norms but become prone to seek alternative values as they enter adolescence, and adults may resume the culturally normative behavioral patterns.…”
Section: Contextual Featuresmentioning
confidence: 66%
See 1 more Smart Citation